Tamibarotene for the treatment of acute promyelocytic leukemia. (September 2014) - Takeshita, Akihiro; Shinagawa, Katsuji; Adachi, Miwa; Ono, Takaaki; Kiguchi, Toru; Naoe, Tomoki
Abstract : Introduction: Acute promyelocytic leukemia (APL) is characterized by a reciprocal translocation between chromosomes 15 and 17 yielding the PML-RARA fusion gene, which deregulates cell proliferation and blocks granulocyte differentiation. All- trans retinoic acid (ATRA) dramatically improved the prognosis of APL, but relatively, small number of relapsing patients achieves second remission with ATRA alone. Areas covered: Tamibarotene, a new synthetic retinoid, is about 10 times more potent than ATRA, chemically more stable than ATRA, with low affinity for cellular RA-binding protein and no detectable binding to RA receptor-γ. Tamibarotene has a significant effect on ATRA-resistant APLs. Some arsenic trioxide (ATO) and gemtuzumab ozogamicin-resistant APLs are reportedly tamibarotene- sensitive. Expert opinion: Tamibarotene was tested in APL-relapsed patients after ATRA-induced complete remission (CR), and 14/24 patients (58%) achieved CR. In an independent trial, 24/39 (61.5%) APL patients achieved CR including 5 newly diagnosed patients and 13 patients who had relapsed twice or more. A prospective randomized study compared tamibarotene with ATRA as maintenance therapy. Four-year relapse-free survival rate was 84% (ATRA) and 91% (tamibarotene) (p = 0.095). In high-risk patients, this became significant (58% ATRA, 87% tamibarotene, p = 0.028). These results suggest tamibarotene should be tested in induction or consolidation therapy and in combination with ATO.